Mengkaji hubungan antara fenomena burnout dan kualiti kehidupan bekerja (KKB) di kalangan penjawat awam di Kuching, Sarawak - Yazwani, Mohd Yazid. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The purpose of this study is to identify the relation ship between burnout and quality work life (QWL) among government servant s . The objective of this study is to identify relationship between selected demographic factors such as age, position, duration of service, leve l of education, monthly salary, and num ber of dependents, duration of marriage and nature of spous e’s occupation with the burnout . Furthermore, this study also aims to identify relationship between QWL such as safety and health, rewards, justice at workplace, chances of self and career building and social relationship in organiz ation with burnout . 60 respondents answered the questionnaire. Analysis using Pearson Product Moment shows that there was a significant relationship between QWL with burnout and there is no significant relationship betwee n selected demographic factors with burnout. T he findings show that there were significant relationship between safety and health, work design, and chances self and career building with burnout . However, no correlations were found between reward, justice a t workplace and social relationship in organization with burnout. This study provides suggestions for the organization and workers to prevent the existing burnout and to increase QWL. In addition, suggest ion future researchers were made for future study.